2016
DOI: 10.1016/j.genhosppsych.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Performance of depression rating scales in patients with chronic kidney disease: an item response theory-based analysis

Abstract: Objective Because there is overlap between somatic symptoms of depression and symptoms of chronic kidney disease (CKD), it is unclear if self-reported depression rating scales can be used accurately in predialysis CKD patients, especially if CKD and other comorbidities are symptomatic. We assessed the performance of two depression scales — the Beck Depression Inventory (BDI) and the Quick Inventory of Depression Symptomatology (QIDS-SR16) — by CKD stage, diagnosis of diabetes and total medical comorbidity burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…However, some studies have reported that patients with stage 4 or 5 CKD are more likely to have depression than those in early stages of the disease (51,53). These inconsistent findings may be attributable to the BPI scale used in our study, which can effectively screen out depression without impacting disease severity (advanced CKD stage or comorbidities) (36). Additional studies with a larger sample of patients at different stages of CKD are needed to clarify the development of depression in CKD.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, some studies have reported that patients with stage 4 or 5 CKD are more likely to have depression than those in early stages of the disease (51,53). These inconsistent findings may be attributable to the BPI scale used in our study, which can effectively screen out depression without impacting disease severity (advanced CKD stage or comorbidities) (36). Additional studies with a larger sample of patients at different stages of CKD are needed to clarify the development of depression in CKD.…”
Section: Discussionmentioning
confidence: 79%
“…Depression was evaluated with the Beck Depression Inventory-II (BDI-II), a 21-item questionnaire with total score ranging from 0-63 (35) and each item scored from 0-3 on a Likert scale. The BDI-II has satisfactory internal consistency and reliability for assessing CKD patients without dialysis (36). In this study, depression was defined as a BDI-II score ≥11 (37).…”
Section: Outcome Measurementmentioning
confidence: 99%
“…A tendency toward overestimation in the diagnosis of depression with the use of some self-administered questionnaires has been described in other studies evaluating patients with various chronic diseases. 65,66 This effect may not be uniform among the questionnaires and may become greater as the depressive symptoms covered by the questionnaire overlap with the symptoms caused by the patient’s disease. 65 In our study, we observed a lower tendency toward overestimation of the prevalence of depression when the HADS-D was used because the items related to the physical manifestations of depression (weight loss, loss of appetite, sleep disturbances, and fatigue), which were present in both the BDI and CES-D, were not contemplated therein.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmaceutical and medical researchers are increasingly adopting IRT to analyze composite scores used for medical diagnosis, such as the Alzheimer's Disease Assessment Scale-Cognitive subscale 3 and others. [4][5][6][7] It has been successfully applied to modeling UPDRS progression in patients with PD as well. [8][9][10] When used in these contexts, latent ability or trait is often interpreted as latent disease severity.…”
Section: Introductionmentioning
confidence: 99%